DEFENSE DIPLOMACY FOR CAPACITY BUILDING: A CASE STUDY OF GARUDA SHIELD - Risalanisa Dwi Putri (Cahaya Ilmu Bangsa, 2025)
This paper discusses the importance of capacity building in increasing the level of a country's defense, and the case study taken is about Indonesia's Garuda Shield. Garuda Shield which has been implemented for years, has its own goals in each exercise. These goals that have been set will be an added value for the Indonesian army. This paper uses a qualitative method. The purpose of this paper is to show the activities to improve Indonesia's defense and security.